A case study of mechanical properties of perovskite-structured Ba0.5Sr0.5Co0.8Fe0.2O3−δ oxygen transport membrane. Issue 2 (February 2018) - Wang, Li; Dou, Rui; Wang, Gong; Li, Yizhe; Bai, Mingwen; Hall, David; Chen, Ying
Abstract: This study has investigated mechanical properties of perovskite-structured Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) oxygen transport membrane. The Young's modulus and fracture toughness are determined by both macroscopic-scale and microscopic-scale methods. Both three-point and ring-on-ring bending tests as macroscopic-scale methods produce broadly similar results with a Young's modulus, which is lower than that measured from micro-indentation method under a 10 N load. Young's modulus and fracture toughness of BSCF show strongly dependent of the porosity. However, the fracture toughness of BSCF is independent of grain size. The fracture toughness determined by macroscopic-scale method is similar with that measured by microscopic-scale method. The crack shape of BSCF under a 10 N load is determined to be a median-radial mode. The intrinsic Young's modulus and fracture toughness are determined to be 105.6 GPa and 1.49 MPa m 0.5, respectively, according the Minimum Solid Area (MSA) model. Annealing decreases the fracture toughness of BSCF between RT and 800 °C.